DYNAMIC NUMERICAL SIMULATION OF DIFFERENT DRILL BIT DIAMETER ON THE POLYURETHANE FOAMS DRILLING - Fernandes, Maria; Fonseca, Elza; Teixeira, Tiago; Jorge, Renato (MATTER: International Journal of Science and Technology, 2017)
Drilling is one of the most common processes involved in different cutting operations and may affect the mechanical properties of the workpiece by creating residual stresses around the opened hole and highly stressed on the newly formed surface. Nevertheless, when it comes to the living tissues, drilling assumes more attention to guarantee a non-invasive procedure. Drilling of bone is common in orthopaedic surgical process, to produce a hole to screw insertion to fix the fractured members for immobilization, or even in dental implant interventions. This work describes a conventional drilling process performed on solid rigid polyurethane foams blocks with similar mechanical properties to the human bone. A dynamic and numerical study was conducted to evaluate the use of different drill diameters (4, 5 and 6mm) on the stresses generated during the process. Different simulations using an explicit dynamic program were performed to assess the level of stresses and the damage effect on the polyurethane foam structure. This program is based on the finite element method and incorporates the dynamic characteristics involved in the drilling process. The main objective of this study is to verify the combination between some drill parameters, that reduce the mechanical damage produced by high stress level during bone drilling. The results permit to assess the influence of the drill bit diameter using a constant feed-rate (75mm/min) and drill speed (600rpm). For these conditions, results show that the smaller drill bit diameter leads to a decrease in the stress level in the foam material during the process.